Predictors of job satisfaction among teachers in Germany during the SARS-CoV-2 pandemic: cross-sectional results of a nationwide online questionnaire - Dicks, Theresa; Eggert, Viktoria; Koestner, Clemens; Zähme, Carolina; Beutel, Till; Kalo, Kristin; Letzel, Stephan; Dietz, Pavel (Frontiers in Psychology, 2023)
During the SARS-CoV-2 pandemic teaching was changed several times to distance learning. To consider the associated stresses and challenges for teachers a nationwide cross-sectional study was performed in March 2021 in which N = 31,089 teachers from Germany participated. A multiple linear regression model with stepwise inclusion of thematically sorted variables (sociodemographic, SARS-CoV-2- & work-related variables) was used to identify relevant predictors of job satisfaction. The analysis revealed that work-related variables were significant predictors of job satisfaction. In the third regression model, when all variables are included the adjusted R2 was 0.364. Overall, the results showed that e.g., work predictability (b = 0.097), influence at work (b = 0.118) and meaning of work (b = 0.212) increased job satisfaction. In contrast, increased emotional exhaustion (b = -0.016), feelings of unfair treatment (b = -0.048), and work family conflicts (b = -0.154) deteriorated job satisfaction. The results indicate that future research should focus especially the work-related topics in more detail and that job satisfaction is a useful concept for analyzing working conditions from a public health point of view.